Writing Organizational Tales: Reflections on Three Books on Organizational Culture - Smircich, Linda (Organization Science, 1995)
I must confess that I’m an organizational culture dropout. It’s been a while since I felt much interest in reading about organizational culture. But Dvora Yanow had framed my task in an intriguing way. She asked me to comment on these three organizational culture books by Trice and Beyer, Kunda, and Martin respectively, as writings that tell stories about organizations and those who research them. Already inherent in this framing is a view that repositions the researcher from scientist to narrator. This view understands the researcher, not as a well-placed observer-scribe using language to mirror the organizational reality he or she witnesses, but as someone already embedded in a language community that shapes what can be said as knowledge.